Нечеткая импульсная стабилизация верхнего положения равновесия маятника на подвижном основании - Денисенко, В.С.; Слынько, В.И. (Прикладная механика, 2013)
Побудовано математичну модель маятника на рухомій основі у вигляді нечіткої імпульсної системи Такагі - Сугено, що дозволило розглядати рух колеса по нерівній поверхні. Одержано достатні умови асимптотичної стійкості верхнього положення рівноваги вказаного математичного маятника. The mathematical model of a pendulum with moving foundation is constructed in the form of Takagi – Sugeno impulsive fuzzy system. This fuzzy model permits to consider the wheel motion in the rough surface. The sufficient conditions of asymptotic stability of the upper position of the pendulum in hand are obtained.